Menyoal Pengawasan Dewan Perwakilan Rakyat terhadap Independensi Pembentukan Peraturan Komisi Pemilihan Umum - Yobel, Teddy Handiar (UI Scholars Hub, 2021)
This paper talks about General Elections Commission independence concept within General Elections Commissions establishment as a part of People Representative Council supervision. The main goal is to search the right stance following the debate of General Elections Commission independence. After the answer emerges, the discovery from the research paper can become reference regarding the answer about General Elections Commissions debate in term of forming General Elections Commission regulations. Specifically, the big question that could be answered from this research is whether General Elections Commission independence disturbed with the consultation obligatory within General Elections Commission regulations establishment? By way of normative, historic, comparative observation that in line of constitutional theory, the writer take a conclusion that General Elections Commission obligatory consultation within General Elections Commission regulations establishment is not disturbing General Elections Commission independence as long the consultation itself is not obstructing and not binding.